Aplicación de un Programa de Actividad Física Recreativa para la Utilización del Tiempo Libre en los Adultos Mayores del Centro de Bienestar del Anciano “El Carmen” de la Ciudad de Armenia (2014)
The present study degree mode Internship is entitled "Implementation of a Program of Physical and Recreational Activities for the Use of Free Time in Older Adult Wellness Center Elder Carmen City Armenia Activities " The intervention was conducted between month of January 2014 and July of 2014 , with the aim of promoting the use of leisure time through a program of physical and recreational activities; the population under study were 16 seniors from elder Wellness Center "El Carmen " in the city of Armenia where he currently 140 Aging , the main problem is a sedentary lifestyle are located , as little physical activities is evidence ( within its motor possibilities ) to help achieve and consolidate between people, from the point of view of quality of life as a concrete expression of human development which is identified with healthy habits , high levels of socialization , self-esteem , sense of membership , reasoning ability and decision making among other values and individual and social contributions ; through the use of free time , because there is no accompaniment or a guide to help them create healthy habits and thus promote health. The intervention of a recreational physical activity program that would promote the use of leisure time, in the context of the Wellness Center of the elderly to contribute to the social projection of Bachelor of Physical Education and Sports was then necessary. The work of recreational physical activities through the use of free time was an issue of great importance because it provided a series of experiences that make the human being within a certain context to create healthy habits, to create more close social relationships and create satisfaction for performing unusual activities in their daily lives.